Anesthesia-Induced Developmental Neurodegeneration: The Role of Neuronal Organelles - Jevtovic-Todorovic, Vesna; Boscolo, Annalisa; Sanchez, Victoria; Lunardi, Nadia (Frontiers in Neurology, 2012)
Exposure to general anesthetics and antiepileptics during critical stages of brain development causes significant neurotoxicity to immature neurons. Many animal, and emerging human studies have shown long-term functional sequelae manifested as behavioral deficits and cognitive impairments. Since general anesthetics and antiepileptic drugs are a necessity, current research is focused on deciphering the mechanisms responsible for anesthesia-induced developmental neurotoxicity so that protective strategies can be devised. These agents promote massive and wide-spread neuroapoptosis that is caused by the impairment of integrity and function of neuronal organelles. Mitochondria and endoplasmic reticulum are particularly vulnerable. By promoting significant release of intracellular calcium from the endoplasmic reticulum, anesthetics cause an increase in mitochondrial calcium load resulting in the loss of their integrity, release of proapoptotic factors, functional impairment of ATP synthesis and enhanced accumulation of reactive oxygen species. The possibility that general anesthetics may have direct damaging effects on mitochondria, resulting in the impairment of their morphogenesis, also has been proposed. This review will present evidence that neuronal organelles are critical and early targets of anesthesia-induced developmental neurotoxicity.